(untitled) (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2024)
The purpose of the study is to assess the social media marketing of Garahe ni Kuya Jo in San Bartolome Novaliches, Quezon City. By assessing social media marketing in terms of product, place, price, and promotion, it also aims to assess the satisfaction in using social media platforms in terms of Instagram, Tiktok, and Facebook; the significant relationship between social media marketing and customer satisfaction; the problem encountered by respondents; and the proposed plan may outline to improve the social media marketing of Garahe ni Kuya Jo. From the result of the study, the respondents describe the social media marketing of Garahe ni Kuya Jo “Agree” in terms of product, place, price, and promotion; the assessment of satisfaction in using social media platforms is also “Agree” in terms of Instagram, Tiktok, and Facebook; There is no significant relationship between the assessment of social media marketing and customer satisfaction; The problems encountered by the respondents are the slow response in inquiries, did not meet the satisfaction online with the actual food and missed chats. Overall, the researchers recommend the company improvements, and they have to present their product with a desirable appearance, improve their marketing through online platforms to gain more positive reviews of their product, review the pricing in combo meals to get a discount, and consider having cash back when purchasing a product.